2015
DOI: 10.1124/jpet.115.228130
|View full text |Cite
|
Sign up to set email alerts
|

Protoporphyrin IX: the Good, the Bad, and the Ugly

Abstract: Protoporphyrin IX (PPIX) is ubiquitously present in all living cells in small amounts as a precursor of heme. PPIX has some biologic functions of its own, and PPIX-based strategies have been used for cancer diagnosis and treatment (the good). PPIX serves as the substrate for ferrochelatase, the final enzyme in heme biosynthesis, and its homeostasis is tightly regulated during heme synthesis. Accumulation of PPIX in human porphyrias can cause skin photosensitivity, biliary stones, hepatobiliary damage, and even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
182
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(186 citation statements)
references
References 155 publications
(154 reference statements)
1
182
0
3
Order By: Relevance
“…The initiation of cell stress can be triggered by the accumulation of a heme biosynthesis intermediate, pro-toporphyrin IX (PPIX) in the liver. PPIX accumulation is associated with hepatotoxic effects mediated by the blocking of bile acid efflux [32, 33]. The liver is responsible for the biosynthesis of 15% of heme in the body [34].…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 99%
“…The initiation of cell stress can be triggered by the accumulation of a heme biosynthesis intermediate, pro-toporphyrin IX (PPIX) in the liver. PPIX accumulation is associated with hepatotoxic effects mediated by the blocking of bile acid efflux [32, 33]. The liver is responsible for the biosynthesis of 15% of heme in the body [34].…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 99%
“…4 PPIX is an intermediate in the heme biosynthesis pathway and its accumulation is the primary cause of liver injury in patients suffering from erythropoietic protoporphyria. 5–7 Rifampicin is a human PXR ligand that induces delta-aminolevulinate synthase 1 (ALAS1), the rate-limiting enzyme regulating heme and porphyrin biosynthesis. 8 However, the role of INH in PPIX accumulation caused by INH and rifampicin co-therapy remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that chronic treatment of mice with INH causes protoporphyrin IX accumulation in the liver, together with the induction of ALAS1 and downregulation of ferrochelatase (Sachar et al, 2016). As depicted in Fig.…”
Section: Chronic Effect Of Drugs On Heme Metabolismmentioning
confidence: 89%
“…On the other hand, protoporphyrin IX-based strategies have been employed for cancer diagnosis and treatment. In this respect, the recently published review by Sachar et al (2016) examines physiological and pathological activities of protoporphyrin IX.…”
Section: Chronic Effect Of Drugs On Heme Metabolismmentioning
confidence: 99%
See 1 more Smart Citation